HER2-related biomarkers predict clinical outcomes with trastuzumab deruxtecan treatment in patients with HER2-expressing metastatic colorectal cancer: biomarker analyses of DESTINY-CRC01 - Salvatore Siena; Kanwal Raghav; Toshiki Masuishi; Kensei Yamaguchi; Tomohiro Nishina; Elena Elez; Javier Rodriguez; Ian Chau; Maria Di Bartolomeo; Hisato Kawakami; Fumitaka Suto; Makito Koga; et al. (Nature Communications)
Abstract DESTINY-CRC01 (NCT03384940) was a multicentre, open-label, phase 2 study that investigated the safety and efficacy of trastuzumab deruxtecan (T-DXd) in patients with human epidermal growth factor receptor 2 (HER2)-expressing metastatic colorectal cancer (CRC). The present exploratory biomarker analysis aims to investigate relationships between biomarkers and clinical outcomes in patients with HER2-positive (immunohistochemistry [IHC] 3+ or IHC 2+ and in situ hybridization [ISH] positive) Cohort A (N = 53) of DESTINY-CRC01. Higher levels of HER2 biomarkers in baseline tissue and liquid biopsies, including HER2 status (IHC/ISH), HER2/CEP17 ratio, HER2 ISH signals, HER2 H-score, plasma HER2 (ERBB2) amplification status, HER2 adjusted plasma copy number, and HER2 extracellular domain correlate with antitumor activity (indicated by objective response rate, progression-free survival, and overall survival) of T-DXd. Baseline circulating tumor DNA (ctDNA) analysis suggests antitumor activity of T-DXd in patients who had baseline activating RAS, PIK3CA, or HER2 mutations detected in ctDNA.